The susceptibility of Atlantic salmon fry to freshwater infectious pancreatic necrosis is largely explained by a major QTL - Houston, Ross D; Haley, Chris S; Hamilton, Alastair; Guy, Derrick R; Mota-Velasco, Jose C; Gheyas, Almas A; Tinch, Alan E; Taggart, John; Bron, James; Starkey, William; McAndrew, Brendan; Verner-Jeffreys, David W; et al. (Heredity, 2010)
Infectious pancreatic necrosis (IPN) is a viral disease with a significant negative impact on the global aquaculture of Atlantic salmon. IPN outbreaks can occur during specific windows of both the freshwater and seawater stages of the salmon life cycle. Previous research has shown that a proportion of the variation seen in resistance to IPN is because of host genetics, and we have shown that major quantitative trait loci (QTL) affect IPN resistance at the seawater stage of production. In the current study, we completed a large freshwater IPN challenge experiment to allow us to undertake a thorough investigation of the genetic basis of resistance to IPN in salmon fry, with a focus on previously identified QTL regions. The heritability of freshwater IPN resistance was estimated to be 0.26 on the observed scale and 0.55 on the underlying scale. Our results suggest that a single QTL on linkage group 21 explains almost all the genetic variation in IPN mortality under our experimental conditions. A striking contrast in mortality is seen between fry classified as homozygous susceptible versus homozygous resistant, with QTL-resistant fish showing virtually complete resistance to IPN mortality. The findings highlight the importance of the major QTL in the genetic regulation of IPN resistance across distinct physiological lifecycle stages, environmental conditions and viral isolates. These results have clear scientific and practical implications for the control of IPN.